Tax evasion and trust - Ronald Wintrobe (The University of Western Ontario, Department of Economics, 2001)
In this paper I take a 'public choice' approach to the problem of tax evasion. Moreover, I assume that people will be more willing to pay their taxes when they trust the government more. Thus, we would expect that tax evasion would be lower, ceteris paribus, the more responsive governments are to their citizens' wishes. Finally, since the level of tax evasion depends on the trust of citizens that other citizens pay their taxes, it follows that there are multiple equilibria, which can be broadly classified into two: one in which, broadly speaking, people assume that others are paying and so most of them also pay, and the other in which the opposite is true.
Keywords: 330; Steuerflucht; Steuervermeidung; Russland